ANALISIS DETERMINAN TINGKAT PENGELUARAN KONSUMSI PANGAN DI JAWA TIMUR - Ahmad Zainuddin; Ratih Apri Utami; Nurul Dwi Novikarumsari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
East Java is a province that has a high population, household consumption expenditure is an important thing to consider. The implication is that there will be an increase in production and investment in East Java. Therefore, household consumption expenditure is one of the determinants of community welfare. This study aims to analyze the structure of household consumption expenditure and the factors that influence food expenditure in East Java. The data used were secondary data from East Java in Figures 2019. This study was analyzed using multiple linear regression analysis. The analysis showed that there has been an increase in the welfare of the people of East Java. This is indicated by an increase in the amount of non-food expenditure is higher than food expenditure. Factors affecting household food expenditure in East Java are GRDP per capita, inflation rate, rice prices, and non-food expenditure. Based on these results it is suggested that the government needs to maintain the stability of prices of goods and services to avoid inflation because inflation will reduce public consumption and have implications for the economy of East Java. Keywords: food expenditure, GDRP per capita, inflation